Riba Dalam Transaksi Kredit Berdasarkan Hadis Ekonomi - Yanti, Ira; Pratiwi , Sevia Diah; Rasta , Juwairiazizah; Amelia , Rizqa (CV. ITTC INDONESIA, 2023)
This study aims to determine usury that occurs in credit transactions. This study uses a qualitative method by taking a library approach, internet searches which are generally carried out indirectly do not jump directly into the field in searching for data sources . Credit is the provision of money made between two parties, usually between a bank and another party that has previously obtained the agreement of both parties where the person who borrows has the right and must repay the loan in accordance with the time and agreement that has been made. Riba is